Impact of United States refugee ban and discrimination on the mental health of hypertensive Arabic-speaking refugees - Albahsahli, Behnan; Bridi, Lana; Aljenabi, Raghad; Abu-Baker, Dania; Kaki, Dahlia A.; Godino, Job G.; Al-Rousan, Tala (Frontiers in Psychiatry, 2023)
Background: Hypertension is a global leading cause of death which disproportionately affects refugees. This chronic disease increases the risk of heart disease, stroke, brain, and other end-organ disease, if left uncontrolled. The 2017 United States (US) travel or "Muslim" ban prevented immigrants and refugees from seven Muslim-majority countries from entering the US, including Syria and Iraq; two major contributors to the global refugee population. As of 2020, the US has admitted more than 133,000 and 22,000 Iraqi and Syrian refugees respectively. Studies on the health effects of this policy on refugees are lacking. This study qualitatively explores the impact of the refugee ban on US-resettled Syrian and Iraqi refugees with hypertension.Methods: Participants were recruited through a federally qualified health center system that is the largest healthcare provider for refugees in San Diego, CA. All participants were Arabic-speaking refugees diagnosed with hypertension from Syria and Iraq. In-depth interviews took place between April 2021 and April 2022. Inductive thematic analysis was used to analyze data from semi-structured interviews.Results: Participants (N=109) include 53 women and 56 men (23 Syrian, 86 Iraqi). The average age was 61.3 years (SD: 9.7) and stay in the US was 9.5 years (SD 5.92). Four themes emerged linking the travel ban's impact on health, in line with the society to cells framework: (1) Family factors: the refugee ban resulted in family separation; (2) Physiological factors: the refugee ban worsened participants' mental health, exacerbating hypertension and perceived health outcomes; (3) Community factors: Perpetuation of Islamophobia, xenophobia, and perceived discrimination were structural barriers with links to poorer health; and (4) Individual factors: Trickle down consequences led to worsened participant self-image and self-perception within their host community.The refugee ban negatively impacted the mental and physical health of US-resettled Arabic-speaking refugees through perceived discrimination, stress, and poor social integration. It continues to have long-lasting effects years after the ban was instated. Centering family reunification within the US Refugee Admissions Program and tailoring interventions through the healthcare and public health systems are warranted to reduce hypertension disparities in this growing and overlooked population.